Evaluating the COVID-19 responses of Belgium, Denmark, Germany, the Netherlands, Sweden, and the United Kingdom, February–June 2020: a counterfactual modeling study - Pieter de Boer; Fuminari Miura; Giske Lagerweij; Jacco Wallinga (BMC Medicine)
Abstract Background Differences in responses to the COVID-19 pandemic among Northwestern European countries have generated extensive discussion. We explore how the impact of the first pandemic wave might have differed, had Belgium, Denmark, Germany, the Netherlands, Sweden, and the UK adopted responses as implemented in the other countries, or had it delayed its own response. Methods The time-varying reproduction number Rt for each country was estimated using time-series of laboratory-confirmed COVID-19 deaths. Counterfactual assessment of the impact of responses was conducted by interchanging the reduction in reproduction number by calendar date between countries from March 13th to July 1st, 2020. The impact of a delayed response was evaluated by lagging the time-series of the reproduction number with 1 day or 3 days. Results The cumulative number of COVID-19 deaths for any of the six countries would have differed substantially, had the response of another country been adopted on the respective calendar date. The order, from the lowest to the highest expected mortality rate, was obtained with the responses of the Netherlands, Belgium, Denmark, the UK, Germany, and Sweden, with a seven- to 12-fold difference between the lowest and highest outcome. Delaying its response by 3 days resulted in approximately doubling the cumulative COVID-19 mortality rate. Conclusions During the fast-growing first COVID-19 wave, small differences in initial epidemiological situations between countries, together with small differences in the timing and effectiveness of adopting COVID-19 response from neighboring countries, result in large variations in mortality rates.